Enhanced Self‐Assembly of Metal Oxides and Metal‐Organic Frameworks from Precursors with Magnetohydrodynamically Induced Long‐Lived Collective Spin States. (2nd June 2014) - Breynaert, Eric; Emmerich, Jens; Mustafa, Danilo; Bajpe, Sneha R.; Altantzis, Thomas; Van Havenbergh, Kristof; Taulelle, Francis; Bals, Sara; Van Tendeloo, Gustaaf; Kirschhock, Christine E. A.; Martens, Johan A.
<x xml:space="preserve">Abstract</x> Magneto‐hydrodynamic generation of long‐lived collective spin states and their impact on crystal morphology is demonstrated for three different, technologically relevant materials: COK‐16 metal organic framework, manganese oxide nanotubes, and vanadium oxide nano‐scrolls. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>